AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN RANDU (Ceiba petandra L. Gaern.) PADA MENCIT JANTAN GALUR Balb/C - yance yance; risha fillah fithria; Yulia Ayu Purnamasari; Kusuma Arum Ningsih; Andri Geger Noviantoro; Suharjono Suharjono (Universitas Wahid Hasyim Semarang, 2012)
ABSTRACTTraditionally, cottonwood's leaves have been used to treat diarrhea. The objective of the study was to investigate antidiarrheal properties of cottonwood’s leaves ethanol extract (EEDR). In addition, this study also wants to reveal the action mechanism of EEDR as antidiarrheal through its activities as antisecretory and antimotility in Balb/C strain male mice. An experimental study performed with randomized matched two-group post test only design approach. EEDR (200-800) mg/kg BW was administered orally to three groups of mice to evaluate the activity of extract as antidiarrheal and antisecretory on castor oil induced diarrhea model in mice. To evaluate the extract as antimotility, EEDR (1.0, 2.0 and 4.0) g/kg BW was provided orally to Balb/C strain male mice. Two other groups received NaCl 0.9 % 20 mL/Kg BW and Loperamide HCl 50 mg/Kg BW. The results showed the EEDR have pharmacological effects as antidiarrhea on Balb/C strain male mice with a mechanism of action as antisecretory and antimotility. The results of this study have been successfully providing the scientific basis of the use of cottonwood’s leaves as antidiarrhea by Indonesian people.Key words : cottonwood’s leaves ethanol extract, castor oil, antidiarrhea, antisecretory